Pengaruh Pelayanan, Kualitas Jaringan, Harga Yang Kompetitif Terhadap Kepuasan Pelanggan Dan Dampaknya Terhadap Kinerja Keuangan PT Global Media Data Prima Cabang Kediri - Merinda Ratna Sari; Marhaendra Kusuma; Siti Isnaniati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of service, network quality, competitive prices on customer satisfaction and the impact on financial performance of pt global media data prima kediri branch. This case study was conducted at PT Global Media Data Prima, Kediri branch. Barokah in 2020-2021 which consists of variables (X) including: service, network quality, competitive prices, variable (Y) customer satisfaction and external variables of financial performance. The sampling technique uses a cluster random sampling technique with random sample types based on area. The results of this study indicate that H1 Service has no effect on customer satisfaction, whereas H2 network quality has no effect on customer satisfaction, and H3 competitive prices have a significant effect on customer satisfaction. Based on the three equations, it proves that customer satisfaction can affect financial performance, the higher the customer satisfaction, the higher the financial performance obtained by the company. The smaller the customer satisfaction, the smaller the financial performance obtained by the company.